Effect of L-tryptophan on growth performance, blood parameters and immunoresponse of Friesian calves - Abu-El-Hamd, MA; Metwally, AM; El-Diahy, YM; Soliman , SH; Ghazy, AM (Journal of the Hellenic Veterinary Medical Society, 2024)
Aim of this study was to investigate the effect of tryptophan supplementation on the immunoglobulin concentration, some blood parameters, growth performance of suckling Friesian calves. A total of 30 newly born Friesian calves with weighing 33.42±1.9 kg were divided into three similar groups, 10 calves in each group. The first group (G1) was served as a control, while the second (G2) and third (G3) groups were supplemented with tryptophan 2 and 4 g/calf/day in suckling milk from birth up to weaning. Results showed that live body weight of calves in G2 and G3 significantly increased by 8 and 9% at 5 weeks, 10 and 11% at 10 and 14 and 16 at 15 weeks compared with those in G1, respectively. The ADG was significantly higher in G2 and G3 than in G1. Plasma immunoglobulins concentrations at different ages of the suckling period were significantly higher in G3 and G2 than in G1. Total immunoglobulins concentrations in plasma of calves in G2 and G3 increased at a range from 10.22 to 18.30% as compared to G1. Haematological parameters were significantly higher values of red (RBCs) and white (WBCs) blood cells counts, PCV value, haemoglobin (Hb) concentration and neutrophils percentage in G2 and G3 than in G1. Concentration of total proteins, albumin and globulin in blood plasma of calves were significantly higher in G2 than in G1. Concentration of total lipids, creatinine, glucose and urea-N were significantly lower in G2 than in G1. It could be concluded that tryptophan supplementation in milk improved growth performance and immune-response of Friesian calves during the suckling period.